SW2D-GPU: A two-dimensional shallow water model accelerated by GPGPU. (November 2021) - Carlotto, Tomas; Borges Chaffe, Pedro Luiz; Innocente dos Santos, Camyla; Lee, Seungsoo
Abstract: Shallow water models are used for simulating flood and lake hydrodynamics. However, the computational cost of those models is often high and require high performance computing. We present the SW2D-GPU: a two-dimensional shallow water model accelerated by General Purpose Graphics Processing Unit. The model is implemented in parallel using CUDA C/C++. We exemplify the use of the model with two case studies: (i) Flood simulation in an urban area and (ii) water level simulation in a lake catchment. We have included potential evaporation in the formulation which expands its application to water level simulations in lakes and reservoirs. The SW2D-GPU model is approximately 34 times faster than its equivalent sequential version. The model can be run in any computer equipped with a NVIDIA GPU. Integrated simulations of surface waters in lake watershed and simulations of floods caused by dam break are some of the potential applications. Highlights: A parallel two-dimensional shallow water model was implemented in CUDA C/C++. Includes application to urban flood and lake water level simulation. The new open source implementation significantly reduces simulation time.